Analisis Akta Wasiat Atas Harta Bersama Yang Dilaksanakan Setelah Suami Meninggal Berdasarkan Putusan Pengadilan Agama No: 2304/Pdt.G/2017/PA Medan - Putra Rizki Akbar; Sunarmi Sunarmi; T. Keizerina Devi Azwar; Edy Ikhsan (Iuris Studia: Jurnal Kajian Hukum, 2021)
A letter of will has to be contained in the deed, in line with the provision stipulated in article 921 of the Civil Code which states that one shall list all the assets that were present at the time of the death of the donor or testator. When heir’s rights are violated, he is allowed to take legal efforts by claiming for his absolute or legal portion through a civil lawsuit to Religious Court, an example of which is the case in the Religious Court Ruling No.2304/Pdt.G/2017/PA Medan. The inherited assets disputed in this ruling belong to Drs. H. AUL and Hj. AHN. When they were still alive, Hj. AHN had drawn up two deeds regulating the provision and sharing of her assets. Due to these deeds, the siblings and nephews of H.AUL, the legitimate husband of Hj. AHN, did not receive any assets. The plaintiffs consider that Defendant I and Defendant II act as if they have full rights over the assets of AUL and AHN, in fact the plaintiff thinks that he is also rightful over the assets of AUL. Reconciliation between both parties has ever been attempted but it failed; thus, the plaintiffs finally file a civil lawsuit to the court. In their lawsuit, they state that they disagree to the action taken by AHN and want to claim for revocation of the deeds in order that they can receive some of the assets inherited by AUL and AHN. This is an analytical descriptive research that describes and analyzes data systematically to provide as conscientious da as possible about humans. The data collection technique employed in this research is combination of documentary study and field research. This research collected secondary data consisting of primary, secondary, and tertiary legal materials. The status of joint property is entitled due to death parting husband and wife as regulated in article 96 paragraph (1) of Islamic Law Compilation which states that half of joint property becomes the right of the other spouse (husband or wife) who lives longer. In this case, the wife has the right to make a will which object belongs to joint property after death of her husband, as long as there is not any violation to the requirements for validation and limitations made by the testator during the drawing up of the deeds. If the limitations are violated, according to Article 201 of Islamic Law Compilation, the will takes only 1/3 of the inheritance. The will drawn up by Defendant II as a Notary has surpassed maximum limit of 1/3 without the consent from Plaintiff I until IX and Defendant III until Defendant VIII as heirs, also, the will was drawn up when AHN was in the state of serious illness which was 1 month after her death. Therefore, the deeds can be revoked because they violated some prevailing regulations